Material degradation of components in polymer electrolyte membrane (PEM) electrolytic cell and mitigation mechanisms: A review. (September 2019) - Khatib, F.N.; Wilberforce, Tabbi; Ijaodola, Oluwatosin; Ogungbemi, Emmanuel; El-Hassan, Zaki; Durrant, A.; Thompson, J.; Olabi, A.G.
Abstract: Hydrogen is increasingly becoming an important element in the quest for clean energy and pollution free transport and this investigation concentrates on one aspect of the hydrogen supply chain which is its production. This work reviews current methods for production of hydrogen and discusses the negative impacts of methods that depend on fossil material to produce hydrogen. The work then reviews the technologies for production of hydrogen using water electrolysis as a clean source of hydrogen production utilising energy from renewables with strong emphasis on the use of polymer electrolyte membrane (PEM) electrolytic cells. The components of PEM electrolyser cell are analysed and their impact on the cell operations are examined. The work discusses the performance of PEM electrolysers and examines the different challenges that face the development of these cells components and the effect of operational conditions on cell construction materials and their longevity. The work analyse published research that discusses the impact cells material deterioration has on cell performance and deviation from optimum operational conditions. Degradation effects at varying operational conditions are discussed along with some mitigation strategies that can be used to improve cells durability and efficiency. This includes the material composition of components in the electrolyser that contribute significantly to the overall efficiency of the cell. The work concludes by suggesting areas for further research to help improve the competitiveness of PEM cells electrolysers. Highlights: Degradation of components for PEM water electrolyser are discussed. Effects of degradation on the overall performance of the electrolyser are captured in this investigation. Mitigating strategies to curb these degradation mechanisms are presented. Prospects of electrolysers as reliable sources of clean hydrogen production are also discussed.